Heterozygous CYP27A1 gene mutation presenting with Achilles tendon xanthoma: a case report - Yushi Oyama; Keishiro Okawa; Takuya Miyagi; Takahiro Sakai; Kyuhachi Otagiri; Hiroshi Kitabayashi (Journal of Medical Case Reports)
Abstract Background Cerebrotendinous xanthomatosis is a rare autosomal recessive lipid storage disorder involving bile acid biosynthesis. Reduced mitochondrial cytochrome P450 enzyme activity leads to abnormal lipid accumulation in various tissues, especially tendons, lenses, and the central and peripheral nervous systems. This condition manifests with systemic symptoms such as neurological disorders, atherosclerosis, tendon xanthomas, and cataracts. Cerebrotendinous xanthomatosis typically presents in individuals with homozygous or compound heterozygous mutations in the CYP27A1 gene because of its autosomal recessive inheritance pattern. However, the phenotypic expression in heterozygous carriers remains uncertain. Case presentation We report a 53-year-old Japanese man who was clinically diagnosed with familial hypercholesterolemia. He presented with marked Achilles tendon xanthomas and refractory hyper-low-density-lipoprotein cholesterolemia. Initiation of intensified lipid-lowering therapy, including inclisiran, resulted in improvement of hyper-low-density-lipoprotein cholesterolemia. Genetic testing revealed heterozygous mutations in CYP27A1 (p.Arg405Gln) and apolipoprotein B (APOB) (p.Pro955Ser). He had no neurological symptoms, cataracts, or other features suggestive of cerebrotendinous xanthomatosis without Achilles tendon xanthomas. Conclusion This case highlights a rare presentation of a potential CYP27A1 heterozygous mutation-related phenotype. The APOB (p.Pro955Ser) variant is associated with reduced low-density-lipoprotein receptor activity, contributing to hyper-low-density-lipoprotein cholesterolemia and Achilles tendon xanthomas. However, this patient’s Achilles tendon xanthoma was thicker than those reported in previous cases with APOB (p.Pro955Ser) gene mutations, suggesting a potential contribution from the CYP27A1 mutation. Although the patient did not exhibit elevated serum cholestanol levels or other cerebrotendinous xanthomatosis features, the marked Achilles tendon thickening raises the possibility that the combination of a heterozygous CYP27A1 gene mutation and an APOB gene mutation contributed to the condition.